The Role of Teacher Competence in Motivating and Enhancing Students’ Interest in Learning Arabic - Aniyatul Nafi'ah; Asep Maulana; Abdurrosyid (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2026)
Teaching and learning activities are interactive processes between teachers and students that aim to convey knowledge and shape students' character. Teachers play a crucial role in enhancing students' motivation and interest in learning, particularly in Arabic language learning. This study aims to examine the extent to which teacher competence influences student motivation and interest in learning Arabic. This study employed a qualitative method with a literature study approach through a review of various relevant theoretical sources. The results indicate that four key teacher competencies—pedagogical, personality, social, and professional—contribute significantly to enhancing student motivation. Competent teachers are able to design an engaging and enjoyable learning environment that encourages active student participation. Furthermore, strategies such as rewarding, implementing healthy competition, and emotional support contribute to enhancing student enthusiasm for learning. The novelty of this study lies in its emphasis on the importance of teacher competence as a determining factor in improving Arabic language learning outcomes, a topic rarely studied compared to other subjects. Therefore, strengthening teacher competence is crucial for creating effective and meaningful Arabic language learning. Abstrak Kegiatan belajar mengajar merupakan proses interaktif yang melibatkan guru dan siswa dalam pengembangan pengetahuan dan pembentukan karakter. Dalam konteks pembelajaran bahasa Arab, kompetensi guru sering dikaitkan dengan motivasi dan minat belajar siswa, namun kajian khusus mengenai hubungan tersebut masih terbatas. Penelitian ini bertujuan untuk menganalisis keterkaitan konseptual antara kompetensi guru dan motivasi serta minat belajar siswa dalam pembelajaran bahasa Arab. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan terhadap 25 sumber ilmiah yang relevan dengan kompetensi guru, motivasi belajar, serta pembelajaran bahasa Arab. Analisis difokuskan pada empat dimensi kompetensi guru, yaitu pedagogik, kepribadian, sosial, dan profesional, serta implikasinya terhadap keterlibatan siswa dalam pembelajaran. Hasil kajian menunjukkan bahwa keempat kompetensi tersebut dikaitkan dalam literatur dengan praktik pembelajaran tertentu, seperti perencanaan pembelajaran yang sistematis, interaksi guru–siswa yang positif, dan penciptaan lingkungan belajar yang suportif, yang berpotensi memengaruhi motivasi dan minat belajar siswa. Penelitian ini tidak mengukur pengaruh secara empiris, tetapi menyajikan sintesis konseptual untuk menjelaskan peran kompetensi guru dalam mendukung keterlibatan siswa pada pembelajaran bahasa Arab. Kajian ini memberikan kontribusi analitis dengan memperjelas posisi kompetensi guru dalam pedagogi bahasa Arab yang masih relatif kurang dikaji dibandingkan bidang studi lainnya.